Please help and include step by step
![Please help and include step by step class=](https://us-static.z-dn.net/files/d18/ed9152040dd8d85c54ff31391e756336.png)
Answer:
[tex]c=-\frac{5}{2}[/tex]
Step-by-step explanation:
[tex]4c+9=\frac{8c+1-(2c-11)}{3}\\ 4c+9=\frac{8c+1-2c-11}{3} \\4c+9=\frac{8c-2c+1+11}{3}\\ 4c+9=\frac{6c+12}{3}\\ 4c+9=\frac{(2*3)c+2^2*3}{3} \\4c+9=\frac{2*3(\frac{2*3c}{2*3}+\frac{2^2*3}{2*3}) }{3} \\4c+9=\frac{2*3(c+2^2^-^1)}{3}\\ 4c+9=\frac{2*3(c+2)}{3}\\ 4c+9=2(c+2)\\4c+9=2c+2*2\\4c+9=2c+4\\(4c+9)+(-9-2c)=(2c+4)+(-9-2c)\\(4c+9)+(-2c-9)=(2c+4)+(-2c-9)\\4c+9-2c-9=2c+4-2c-9\\4c-2c+9-9=2c-2c+4-9\\2c=-5\\\frac{2c}{2}=-\frac{5}{2} \\c=-\frac{5}{2}[/tex]
hope this helps.